Plasmodium falciparum sexual differentiation in malaria patients is associated with host factors and GDV1-dependent genes - Miho Usui; Surendra K. Prajapati; Ruth Ayanful-Torgby; Festus K. Acquah; Elizabeth Cudjoe; Courage Kakaney; Jones A. Amponsah; Evans K. Obboh; Deepti K. Reddy; Michelle C. Barbeau; Lacy M. Simons; Beata Czesny; et al. (Nature Communications, 2019)
Here, the authors quantify early gametocyte-committed ring (gc-ring) stage Plasmodium falciparum parasites in 260 malaria patients 10 days before maturation to transmissible stage V gametocytes, and show that the ratio of circulating gc-rings is positively correlated with parasitemia and negatively correlated with body temperature.